Marketing for the health and fitness industry : technology, strategy and value - Williams-Burnett, Nicola; Marriott, Hannah R. (Emerald Publishing Limited, 2025)
Marketing for the Health and Fitness Industry: Technology, Strategy and Value provides an encompassing exploration of the current landscape in health and fitness marketing, expertly navigating the evolving challenges and transformations shaping the industry. Authored by a seasoned health and fitness practitioner, this monograph seamlessly weaves together diverse subjects such as participation trends, consumer behaviors, consumption values, and technology's impact. Spanning from the fitness boom of the 1970s to the present, the text offers a holistic perspective, offering practical insights into this dynamic and fast-paced market.